Advancing knowledge and spearheading social and political transformation: evidence from Ethiopian Journal of Social Sciences, the December 2023 issue - Minale, Amare Sewnet; Bazezew, Arega (Ethiopian Journal of Social Sciences, 2023)
Based on information obtained from the Ministry of Education, the number of higher education institutions in Ethiopia has significantly increased over the past two decades. Similarly, higher education institutions in Ethiopia have the responsibility of undertaking research and providing community services at national and local levels. This implies that carrying out research and publishing its output in a peer-reviewed journal is one of the criteria for promotion of the academic staff and graduation of PhD students (MOE, 2016). Hence, professors and graduate students should try to publish their work in peer-reviewed and indexed journals. It is also to note that the research output should solve societal problems, instead of gathering dust on library shelves. In this regard, Ethiopian Journal of Social Sciences aims to achieve this objective.